Developing the LDi and LCi Geomagnetic Indices, an Example of Application of the AULs Framework - C. Cid; A. Guerrero; E. Saiz; A. J. Halford; A. C. Kellerman (Space Weather)
Abstract The Application Usability Level (AUL) framework has been recently introduced as an efficient and effective way to track progress toward the needs of a user for a specific application. This paper is an example of how the AUL framework facilitates communication between the industry users of space weather research and researchers for developing a product. The products are two new geomagnetic indices fully approved for on‐demand use: the LDi index, for nowcasting local geomagnetic disturbances, and the LCi index, as a proxy for the geomagnetically induced currents risk.